Study of Chemical Composition and Evaluation of Anti-hypertensive Effect of A Fixed Oil Extracted from Linum usitatissimum grains - Halima, Oulad Ali; Mebarka, Belboukhari; Nasser, Belboukhari; Khaled, Sekkoum; Kawther, Al Sid Chikh (Journal of Food and Pharmaceutical Sciences, 2024)
Globally grown flax seed is regarded as an oilseed with numerous medicinal and health are the outcomes of the physico-chemical analyses: pH value: 0.476; saponification index: 168.3; KOH/g: 28.05; peroxide index: 174; density: 0.951; refractive index: 1.482 at 18.1°C and 1.485 at 18.2°C; peroxide index: 1.70 at 0.96, 1.70 mg/100; all are related to the peroxide index. In this study we tried to test the ” anti-hypertension “ activity of this oil by simulating a blood cycle in the laboratory which allowed us to determine the variation in blood pressure as a function of the volume of oil injected into the blood cycle from 17.4 to 14.10. benefits such as: lowering blood pressure, blood sugar, decreasing the risk of neurological and obesity-related illnesses. The objective of this study is to extract the linseed oil and to characterize it chemically and physically; by pressing the seeds into two different temperatures : 67°C and 90°Coil yields ; 24% and 29% were obtained from linseed. The followings